Sharia Compliant Fintech in the Digital Era: Regulation Challenges and Growth Enablers - Utari, Septi; Samsuri, Andriani; Ahsan, Muhamad; Md Tahir, Raziah; Sukmana, Dedy (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The development of Islamic financial technology (fintech) has transformed the delivery of Sharia-compliant financial services in the digital era. Islamic fintech offers broader financial inclusion, operational efficiency, and ethical financial services aligned with Islamic principles. However, the industry still faces challenges related to regulation, cybersecurity, financial literacy, and technological readiness. This study aims to analyze the major regulatory challenges and supporting factors influencing Islamic fintech growth through a systematic literature review approach. The study employed the PRISMA framework to identify, evaluate, and synthesize relevant studies published between 2019 and 2024. Data were collected from Scopus, Web of Science, ScienceDirect, SpringerLink, and Google Scholar databases. A total of 65 publications were included in the final analysis. The findings indicate that government support, regulatory sandboxes, blockchain integration, consumer trust, and strategic partnerships are important drivers of Islamic fintech growth. Meanwhile, inconsistent regulations, cybersecurity risks, and low financial literacy remain major barriers to sustainable development. This study concludes that adaptive regulations, digital literacy improvement, and technological innovation are essential to strengthen Islamic fintech ecosystems and improve financial inclusion in Muslim-majority countries.